Memorable tourism experience of heritage-local food on tourist behavior: Mediating role of destination image and satisfaction - Hidayat, Indra Iryanto Nur; Mukarromah, Nur Zakiyah; Putri, Windi Mahendra; Nurhandini, Nurhandini; Meidawati, Devi (Asian Management and Business Review, 2024)
The primary purpose of this research is to find out how memorable tourism experiences influence revisit intention and recommendation intention of tourists who have visited to enjoy historical tourism and taste Rajamangsa local cuisine in Kebondalem Kidul Cultural Tourism Village, with destination image and satisfaction as mediating factors. This research uses a quantitative and descriptive-analytical approach, using a 5-point Likert scale for measurement. Non-probability sampling, specifically judgment sampling, was used to collect primary data. The sample consisted of 245 tourist respondents who had visited to enjoy historical tourism and taste Rajamangsa local cuisine in Kebondalem Kidul Cultural Tourism Village. Structural Equation Modeling (SEM) with SmartPLS 3.2.9 was used as the analysis tool. The findings of this study indicate that memorable tourism experiences directly influence destination image, travel satisfaction, local food tasting, and revisit intention when visiting Kebondalem Kidul Cultural Tourism Village. In addition, destination image travel satisfaction and local food tasting partially mediate between memorable tourism experiences and revisit intention and fully mediate between memorable tourism experiences and recommendation intention of tourists in cultural tourism destinations. This research highlights the positive impact of memorable tourism experiences on revisit intentions, destination perceptions, and traveller satisfaction. The practical implications are significant for tourism management in increasing satisfaction and building a positive destination image. However, this study has limitations regarding location coverage and online data collection methods. Future research must consider geographic variation, data collection methods, and other factors influencing tourism experiences.